The Faith(fulness) of Christ in Romans?: Some Remarks - Feník, Juraj (Ephemerides theologicae Lovanienses, 2023)
Literary context, both immediate and remote, is a crucial factor in determining the meaning of πίστις Χριστοῦ. This study focuses on the Letter to the Romans as the primary interpretative framework for the πίστις Χριστοῦ formulations in 3,22 and 3,26. It shows that various contextual arguments can be marshalled in order to significantly weaken the case for a subjective reading of the phrase. Especially noteworthy is the fact that Paul does not connect Christ’s death, as described in this letter, to Christ’s inner disposition shown through his faith or faithfulness. Overall, the context of Romans does not favor the interpretation of πίστις Χριστοῦ as a subjective genitive, that is, as faith or faithfulness exercised by Jesus Christ.